Synthesis of single metallic crystal in microgravity simulated by static magnetic field. (December 2022) - Lin, Wenhao; Liu, Ying; Zhou, Bangfei; Cai, Hao; Shen, Zhe; Ren, Weili; Lei, Zuosheng; Liu, Chunmei; Zheng, Tianxiang; Zhong, Yunbo; Lu, Bo; Zhang, Lei; et al.
Abstract: Static magnetic field is useful in processing materials with various microstructures. A self-designed gravity-assisted automatic docking device was used to study diffusion in liquid Al-Cu melts under various SMFs up to 22 T. SMF reduces the coefficient of interdiffusion ( D AlCu ) by damping the melt convection, which is more efficient with a horizontal SMF than a vertical SMF. A simulated microgravity is achieved when the SMF is greater than the critical 3 T. The simulated microgravity is in favor of growing a single α-Al dendrite in Al-Cu melt. The physical mechanism, which is called the diffusion-limited favored single crystal growth, is established. The present work provides a potential method in processing the single metallic crystal rapidly in the future. Graphical abstract: Image, graphical abstract